2016
DOI: 10.1097/01.mjt.0000434042.62372.49
|View full text |Cite
|
Sign up to set email alerts
|

Renal Drug Dosage Adjustment According to Estimated Creatinine Clearance in Hospitalized Patients With Heart Failure

Abstract: It is of clinical importance to determine creatinine clearance and adjust doses of prescribed drugs accordingly in patients with heart failure to prevent untoward effects. There is a scarcity of studies in the literature investigating this issue particularly in patients with heart failure, in whom many have impaired kidney function. The purpose of this study was to determine the degree of awareness of medication prescription as to creatinine clearance in patients hospitalized with heart failure. Patients hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…The latter finding can be explained by the fact that beta-blockers were among the most commonly prescribed class of medication requiring adjustment similar to the results obtained by Bailie et al 23. Furthermore, the inadequate adjustment rate of beta-blockers in the present study was 83.6% far more than the 3.78% attained with Altunbas et al 19…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The latter finding can be explained by the fact that beta-blockers were among the most commonly prescribed class of medication requiring adjustment similar to the results obtained by Bailie et al 23. Furthermore, the inadequate adjustment rate of beta-blockers in the present study was 83.6% far more than the 3.78% attained with Altunbas et al 19…”
Section: Discussionsupporting
confidence: 91%
“…Altunbas et al . reported significantly lower rates of 12.6%, but the rate was explained by authors by the fact that the study patients had higher degrees of renal dysfunction, compared to other studies, and thus required nephrology consultation and more careful drug prescription 19. Another similar study was carried out at a governmental hospital in Palestine, indicated that only 26.42% of medications were found to be appropriately adjusted, compared to 73.58% inappropriately adjusted medication orders 20…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Whereas, Altunbas et al reported considerably lower prevalence of medication dosing errors (12.6%), however the authors explained that majority of the study participants had renal impairment thereby necessitating nephrology consultation and optimized drug regimen, which could limit the generalizability of study findings. 36 In developed nations, the active involvements of clinical pharmacists coupled with computerized dosage optimization systems are primarily responsible for the appropriate medication therapy. Most automated dosage adjustment systems automatically alert the healthcare professionals including physicians and clinical pharmacist regarding renal function status and the need for dose optimization.…”
Section: Discussionmentioning
confidence: 99%